Caracterización del fitoplancton y estado trófico de la laguna Sauce Grande (provincia de Buenos Aires, Argentina) en el otoño de 2010 - Ferrer, Nora Cristina (2012)
The composition and abundance of the phytoplankton in the Sauce Grande Shallow Lake were studied during the autumn of 2010. Three sampling sites were established: In the output Sauce Grande River (E1), at the entrance of the Sauce Grande River in the water body (E2) and in the deepest sector of the water body (E3). Sixty taxa were identified, belonged to Chlorophyta (50%), Heterokontophyta (27%), Cyanobacteria (20%) and Dinophyta/Euglenophyta (3%). Phytoplankton abundance ranged between 84500 and 340600 ind/ml. No differences were observed in total phytoplankton abundances among sampling stations, but significant differences among sampling dates were found. Planctonema lauterbornii Schmidle (Chlorophyta) was the dominant species with abundances up to 70600 ind/ml. Several salinity indicators (as Chaetoceros muelleri, Cyclotella aff. meneghiniana and Protoperidinium achromaticum) and eutrophication indicators (as Microcystis aeruginosa and Pediastrum boryanum) were registered. Besides, representatives of Cyanobacteria putative toxic-bloom producers (as species of Anabaena, Anabaenopsis, Aphanocapsa and Microcystis) were identified. This shallow lake is classified as eutrophic according to Carlson TSI based on chlorophyll a. The high phytoplankton abundance and the low Secchi disk readings allow defining the Sauce Grande Shallow Lake as “turbid” and phytoplankton dominated.